Evaluation of shelf life of some value added organic formulations of Trichoderma harzianum (The Journal of Plant Protection Sciences, 2021)
Shelf life of Trichoderma harzianum (Th1AN) was studied during 2007-08 in some organic formulations like vermicompost, leaf manure, rice bran and FYM and also their combinations with two oil cakes, neem and mustard cake. The growth was estimated in terms of colony forming unit (c.f.u.)/g of substrate up to 120 days at 30 days interval. In all organic products or their amendment with oil cakes c.f.u. increased up to 60 days and then gradually declined. Among the four organic media, vermicompost retained 21.3 x 107 c.f.u./g at 120 days where as leaf mold, FYM and rice bran retained 20.1 x 107 c.f.u./g, 17.3 x 107 c.f.u./g and 15.1 x 107c.f.u. /g of substrate respectively at 120 days of incubation. When oilcake was amended with organic material, vermicompost + mustard cake produced high population of the antagonist upto 60 days.
Keywords: Shelf life; Trichoderma harzianum; organic substrate; oil cake.